Self‐Assembly of an Anion‐Binding Cryptand for the Selective Encapsulation, Sequestration, and Precipitation of Phosphate from Aqueous Systems. Issue 40 (7th September 2018) - Rice, Craig R.; Slater, Christopher; Faulkner, Robert A.; Allan, Robert L.
Abstract: The self‐assembled trimetallic species [L2 Cu3 ] 6+ contains a cavity that acts as a host to many different anions. By using X‐ray crystallography, ESI‐MS, and UV/Vis spectroscopy we show that these anions are encapsulated both in the solid state and aqueous systems. Upon encapsulation, the anions Br −, I −, CO3 2−, SiF6 2−, IO6 3−, VO4 3−, WO4 2−, CrO4 2−, SO4 2−, AsO4 3−, and PO4 3− are all precipitated from aqueous solution and can be removed by filtration. Furthermore, the cavity can be tuned to be selective to either phosphate or sulfate anions by variation of the pH. Phosphate anions can be removed from water, even in the presence of other common anions, reducing the concentration from 1000 to <0.1 ppm and recovering approximately 99 % of the phosphate anions. Abstract : The self‐assembled trimetallic species [L2 Cu3 ] 6+ contains a cavity that acts as a host to many different anions, and the anions Br −, I −, CO3 2−, SiF6 2−, IO6 3−, VO4 3−, WO4 2−, CrO4 2−, SO4 2−, AsO4 3−, and PO4 3− are all encapsulated and precipitated from aqueous solution and can be removed by filtration. Furthermore, the cavity is also selective to phosphate anions and selectively and efficiently removes them from water.